Malignant transformation of mature cystic teratoma of the ovary. Issue 12 (2nd September 2022) - Atwi, Doaa; Kamal, Maria; Quinton, Michael; Hassell, Lewis A.
Abstract: Mature cystic teratoma is the most common ovarian germ cell neoplasm. Malignant transformation is a rare occurrence, accounting for 1.5%–2% of cases. Malignant changes can arise from any constituent tissue of a teratoma; however, squamous cell carcinoma is the most common histologic type seen, followed by adenocarcinoma and sarcoma respectively. Tumor marker concentration levels, age, and the tumor maximum diameter are predictive indicators for malignant transformation. Proper diagnosis includes recognizing the possibility of malignant transformation versus excluding other differential options, such as metastasis. Primary cytoreductive surgery, adjuvant chemotherapy, and radiotherapy are the current treatment methods. The aim of the review is to discuss the clinical and pathologic features of malignant transformation within mature cystic teratomas, while reviewing the reported malignant types, differential diagnoses, and treatment options. Data sources include review of pertinent peer‐reviewed literature on malignant transformation of mature cystic teratoma and cases seen in authors' institutional practice. Mature cystic teratomas are a commonly encountered benign ovarian tumor. However, the possibility of malignant transformation should remain in consideration, especially with given clinical or pathologic features: increased patient age, tumor size, or tumor marker levels. Thorough sampling of solid tumor foci can help identify malignant components. Awareness and proper diagnosis, along with early detection and clinical management, shows improved patient outcomes.